Effect of Pinching and Growth Retardants on Growth and Flowering in African Marigold Cv. Pusa Narangi Gainda - K Sasikumar; V Baskaran; K Abirami (Journal of Horticultural Sciences, 2015)
A study on the effect of pinching and application of growth retardants on growth and flowering in African marigold cv. 'Pusa Narangi Gainda' was carried out in the experimental field of Division of Floriculture and Landscaping, Indian Agricultural Research Institute, New Delhi. Treatments comprised pinching, CCC applied at 1000ppm, 1500ppm or 2000ppm, MH at 500ppm, 1500ppm or 2000ppm; B-9 at 500ppm, 750ppm or 1000ppm, and a Control (no pinching). CCC at 2000ppm recorded minimum plant height (46.0cm), maximum plant-spread (56.0cm) and maximum number of branches (19.0), whereas, maximum plant height (67.0cm), minimum plant-spread (29.66cm) and minimum number of branches (5.33) were recorded in Control (non-pinching). As for flowering and yield, application of CCC at 2000ppm recorded maximum flowering-duration (25.33 days), number of flowers per plant (40), single-flower weight (119.46g), flower yield per plant (408.10g), flower yield per unit area (17.83t/ha) and seed yield per plant (17.80 g), Maximum flower diameter (7.93cm) was recorded with application of CCC 2000ppm, whereas, minimum was recorded with pinching (6.2cm). Spray of growth retardants enhanced flower yield compared to that in Control (no pinching). Maximum shelf-life of flower was recorded with CCC 2000ppm (3.66 days), whereas, minimum was recorded with pinching and non-pinching (2.33 days). Thus, application of CCC at 2000ppm is superior to other treatments tested for increasing flower yield in marigold.